Ownership versus Environment : Disentangling the Sources of Public Sector Inefficiency - Bartel, Ann P.; Harrison, Ann E. (World, 2015)
The authors compare the performance of public and private sector manufacturing firms in Indonesia for 1981-95. They analyze whether public sector inefficiency is due primarily to agency-type problems (ownership) or to the business environment in which public enterprises operate, as measured by soft budget constraints or barriers to competition. They nest the two alternatives in a production function framework. The results, obtained from fixed-effects specifications, provide support for both models. The business environment matters. Only public enterprises that received loans from state banks or those shielded from import competition performed worse than private enterprises. Ownership matters. For a given level of import competition or soft loans, public enterprises perform worse than their counterparts in the private sector. Eliminating soft loans to Indonesia's public enterprises would raise total factor productivity by 6 percentage points; the same result could be achieved by increasing import penetration by 15 percentage points. The authors show that these findings are not due to selection effects for either privatization or the receipt of soft loans.